Service Experience Capability Effects on Patient Satisfaction Through Expectation Disconfirmation in Primary Healthcare - Saifur Rahman; Finorina Finorina; Iskandar Ali Alam; Andala Rama Putra Barusman; Habiburahman Habiburahhman (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to develop and test a model explaining the effect of Service Experience Capability (SEC) on patient satisfaction through disconfirmation mediation in primary inpatient healthcare services. SEC is conceptualized as a higher-order organizational capability that integrates organizational processes, technology, and patient interactions to enhance service experiences.Research Methodology: This study employed a quantitative explanatory survey with a cross-sectional design involving 150 patients from Rahayu Main Inpatient Clinic and Ciko Main Inpatient Clinic in Lampung Province, Indonesia. Data were collected using purposive sampling and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS version 4.1.1.2.Results: The findings show that SEC positively and significantly affects disconfirmation and patient satisfaction. Disconfirmation also significantly influences satisfaction and partially mediates the relationship between SEC and patient satisfaction, emphasizing the role of experience management in shaping patient evaluations.Conclusions: Patient satisfaction is influenced not only by clinical service quality but also by organizational capability in managing service experiences.Limitations: This study is limited to two inpatient clinics and a cross-sectional design.Contributions: It contributes to healthcare management literature by positioning SEC as a higher-order capability and explaining its role in improving patient satisfaction through disconfirmation mechanisms.